Interaction of PICK1 with C-Terminus of Growth Hormone-Releasing Hormone Receptor (GHRHR) Modulates Trafficking and Signal Transduction of Human GHRHR - Yuriko Katsushima; Takeya Sato; Chika Yamada; Moe Ito; Yuki Suzuki; Eishin Ogawa; Izumi Sukegawa; Jun Sukegawa; Kohji Fukunaga; Teruyuki Yanagisawa (Elsevier, 2013)
Release of growth hormone (GH) from the somatotroph is regulated by binding GH-releasing hormone (GHRH) to its cognate receptor (GHRHR), one of the members of the G protein-coupled receptor (GPCR) superfamily. Proteins bound to the carboxy (C)-terminus of GPCR have been reported to regulate intracellular trafficking and function of the receptor; however, no functionally significant protein associated with GHRHR has been reported. We have identified a protein interacting with C-kinase 1 (PICK1) as a binding partner of GHRHR. In vitro binding assay revealed the PDZ-domain of PICK1 and the last four amino acid residues of GHRHR were prerequisite for the interaction. Further, in vivo association of these proteins was confirmed. Immunostaining data of a stable cell line expressing GHRHR with or without PICK1 suggested the C-terminus of GHRHR promoted cell surface expression of GHRHR and PICK1 affected the kinetics of the cell surface expression of GHRHR. Furthermore, cAMP production assay showed the C-terminus of GHRHR is involved in the regulation of receptor activation, and the interaction of GHRHR with PICK1 may influence intensities of the signal response after ligand stimulation. Thus, the interaction of the C-terminus of GHRHR with PICK1 has a profound role in regulating the trafficking and the signaling of GHRHR. [Supplementary Figure: available only at http://dx.doi.org/10.1254/jphs.12287FP] Keywords:: protein interacting with C-kinase 1 (PICK1), growth hormone-releasing hormone receptor (GHRHR), interaction, trafficking, signaling